COVID-19: INSTITUTIONAL PREREQUISITES FOR NEW FORMS OF RENT-SEEKING IN THE TOURISM INDUSTRY - Ivanka DIMITROVA; Minko GEORGIEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article examines the institutional problems and new forms of rent - seeking in the tourism sector of Bulgaria in terms of changes in the impact of Covid -19 after the declared state of emergency in the country on March 13, 2020. The study applies: (1) analysis of search conditions on rent; (2) the role of Covid -19 and the creation of new forms of rent-seeking; (3) negative economic effects are presented by measuring rents. The impact of Covid-19 measures and legislative initiatives help to create rent-seeking.